Association of Serum Magnesium and Serum Calcium Levels in Acute Myocardial Infarction Associated with Type 2 Diabetes Mellitus (Bangladesh Journal of Medical Biochemistry, 2025)
This study was done to see the association of serum magnesium and serum calcium in acute myocardial infarction with type 2 diabetes mellitus. This cross sectional study was done on 50 diagnosed patients of acute myocardial infarction with type 2 diabetes and 50 acute myocardial infarction patients without type 2 diabetes mellitus in the department of Biochemistry, Dhaka Medical College, Dhaka from July 2014 to June 2015. Adult patients of acute myocardial infarction with type 2 diabetes mellitus aged between 35 to 60 years, both male and female, attending CCU of Dhaka Medical College Hospital & National Institute of Cardiovascular Diseases and Hospital were selected as the study subjects according to selection criteria. Informed written consent from all study subjects was taken after full explanation of the procedure. The serum magnesium and serum calcium and fasting plasma glucose of study subjects were assessed. The serum magnesium and serum calcium levels were statistically compared to observe the relation with patients of acute myocardial infarction with or without type 2 diabetes mellitus. Serum magnesium showed negative significant correlation (r=-0.710; p=0.001) with fasting plasma glucose of the study patients ? and negative correlation (r=-0.266; p=0.062) in patients with AMI with diabetes mellitus. Serum calcium showed negative significant correlation (r=-0.746; p=0.001) with fasting plasma glucose of the study patients ? and negative significant correlation (r=-0.431; p=0.002) in patients with acute myocardial infarction with diabetes mellitus. The hypomagnaesemia and hypoglycaemia were observed in patients with acute myocardial infarction with type 2 diabetes mellitus with statistical significance. It is very much important to evaluate these parameters as early as possible on arrival of the patients in hospital to reduce cardiac death. Because hypomagnaesemia and hypocalcaemia in the initial phase of post-acute myocardial infarction is very critical, as ventricular tachyarrhythmia, sudden cardiac death and reinfection and neuromuscular disturbance are the usual outcomes.Bangladesh J Med Biochem 2021; 14(1): 03-11